2009
DOI: 10.1088/0953-4075/42/10/105102
|View full text |Cite
|
Sign up to set email alerts
|

On some aspects of changing the sign of the dipole moment functions of diatomic molecules

Abstract: Ab initio calculations of asymptotic dipole moment functions of some diatomic molecules at R → 0 have been carried out. It was achieved that in a range of small internuclear separations, the dipole moment functions of the molecules CO, NO, BF and BeNe for ground electronic states have an additional change of the sign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…It should be emphasized that the values of μ(r e ) and α(r e ) for diatomic molecules were comprehensively explored and tabulated elsewhere [48][49][50][51][52]. At the same time, the DMF, determined over a broad range of r, is also of great theoretical importance because it can highlight features of the electronic structure of a molecule [53,54]. With respect to the dependence of the polarizability on internuclear distance α(r), it comes into play in the theory of low-energy electron-molecule scattering and in the theory of vibrational excitation of molecules by electron impact [10,55].…”
Section: Introductionmentioning
confidence: 99%
“…It should be emphasized that the values of μ(r e ) and α(r e ) for diatomic molecules were comprehensively explored and tabulated elsewhere [48][49][50][51][52]. At the same time, the DMF, determined over a broad range of r, is also of great theoretical importance because it can highlight features of the electronic structure of a molecule [53,54]. With respect to the dependence of the polarizability on internuclear distance α(r), it comes into play in the theory of low-energy electron-molecule scattering and in the theory of vibrational excitation of molecules by electron impact [10,55].…”
Section: Introductionmentioning
confidence: 99%
“…AlCl, AlF, AlH, BCl, BF, CO, CS, HBr, HCl, HF, MgHe, NaLi, SiO, SiS, YBr). [97][98][99][100] Such observation is of relevance as it reflects the process of electron charge transfer inside the molecule. Moreover, on the basis of extensive theoretical studies Maroulis and co-workers have found that the variation of bond length results in substantial changes of (hyper)polarizability, which are quite distinct for different molecular systems.…”
Section: Resultsmentioning
confidence: 99%
“…At this stage it should be mentioned that the R-dependence brings forth important features of the static electric properties (m, a, b and g) of molecular systems, as it has been already disclosed in many valuable scientific works. 10,[92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108] Although it is difficult to draw one general conclusion emerging from these studies, there are several important observations worth underscoring. Among others, the sign inversion of the dipole moment with the change in the internuclear separation is characteristic for various molecular systems (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…A linear dipole function, which may be valid for small oscillation amplitudes, implies a force that is independent of the relative distance of the atomic pair. However, realistic molecular permanent dipoles generally have non-linear spatial behavior, leading to a force acting on the molecule which does depend on the inter-nuclear distance [25][26][27]. There is, in fact, an increasing interest in studying the role of the dipole function in controlling the dynamics of molecular systems [28,29].…”
Section: Introductionmentioning
confidence: 99%